The Effect of Flashcard Learning Media in Developing Cognitive Children Aged 5-6 Years in Al-Mauizhah Kindergarten, Silau Jawa Village, Bandar Pasir Mandoge District, Academic Year 2022/2023 - Nurul Husna Saragih; Kamtini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of using flashcard learning media in developing the cognitive development of children aged 5-6 years in Al-Mauizhah Kindergarten, Silau Jawa Village, Bandar Pasir Mandoge District, Academic Year 2022/2023. This type of research is a quantitative research (quasi experiment) with the form of One Group Pretest-Posttest Design. The population of this study were all class B children at Al-Mauizhah Kindergarten, Silau Jawa Village, Bandar Pasir Mandoge District, 2022/2023 Academic Year, with a total of 30 children. The sampling technique is by looking at the list of the lowest scores from the teacher's data, namely 10 children. The data collection instrument in this study used observation and documentation sheets. Data analysis technique using non-parametric statistical Wilcoxon test. The results showed that the flashcard media from the calculation of the Wilcoxon Rank-K Test, the Z value was close to -2.825b and the p value (Asymp.Sig 2-tailed) was close to .005. It can be concluded that the